2000
DOI: 10.1016/s0008-6363(99)00272-2
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction by nitric oxide in adult cardiomyocytes via cGMP-signaling and its impairment after simulated ischemia

Abstract: NO induces apoptosis in a cGMP dependent manner in isolated adult cardiomyocytes whereas induction of necrosis seems cGMP-independent. After simulated in vitro ischemia the activation of soluble guanylyl cyclase by NO is transiently inhibited resulting in a transient anti-apoptotic protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
67
0
3

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 21 publications
12
67
0
3
Order By: Relevance
“…Similar rates were given in other experimental MI studies. [27][28][29] In our study both in the 2 nd and 28 th day, the most intensive apoptosis was determined in the border zone of infarct. Palojoki et al reported that apoptosis in the border zone continues until the 12 th week.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Similar rates were given in other experimental MI studies. [27][28][29] In our study both in the 2 nd and 28 th day, the most intensive apoptosis was determined in the border zone of infarct. Palojoki et al reported that apoptosis in the border zone continues until the 12 th week.…”
Section: Discussionsupporting
confidence: 45%
“…Although the effects of NO on apoptosis have been evaluated in many studies, the results of these studies were controversial. [26][27][28][29] However, NO mediated effects of nebivolol on apoptosis after MI has not been investigated before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic intervention showing antioxidant or free radical scavenging activity should exert beneficial effects against oxidative stress associated with various cardiovascular diseases (CVDs) [27]. Possible mechanisms of tincture of Crataegus (TCR) include preventing the increase in lipid peroxidation and activity of marker enzymes, preventing the isoproterenol-induced decrease in antioxidant enzymes in the heart, and increasing the rate of ADP-stimulated oxygen uptake and respiratory coupling ratio in isoproterenol-induced rats [28].…”
Section: Cardiovascular Effectmentioning
confidence: 99%
“…[93,94] In some cells, the pro-death signaling is initiated by cGMP, [95,96] while in others (including hepatocytes) cGMP inhibits apoptosis. [37,97,98] …”
Section: Chemical Fate Of No• In Biological Systemsmentioning
confidence: 99%